APPLICATION OF DIMENSIONAL ANALYSIS IN CALIBRATION OF A DISCRETE ELEMENT MODEL FOR ROCK DEFORMATION AND FRACTURE - Fakhimi A.; Villegas T. (My University, 2006)
A discrete element approach was used in the simulation of rock fracture. The numerical synthetic material was made of rigid circular particles or cylinders that have interaction through normal and shear springs. The cylinders were bonded to each other at the contact points to withstand the applied loads. To characterize the microscopic properties of this synthetic material, a dimensional analysis approach was presented. It was shown that the dimensionless parameters and graphs obtained were useful tools for fast and efficient calibration of a synthetic material. This calibration method was employed for finding a numerical model for Pennsylvania Blue Sandstone. The numerical model could mimic many deformational and failure characteristics of the sandstone in both conventional and some non-conventional stress paths.
Keywords: ROCK FRACTURE; DISCRETE ELEMENT METHOD; DIMENSIONAL ANALYSIS; CALIBRATION